Diagnostic performance and neural basis of the combination of free‐ and pre‐drawn Clock Drawing Test. (12th March 2022) - Imai, Ayu; Matsuoka, Teruyuki; Kato, Yuka; Narumoto, Jin
Abstract: Objectives: This study aimed to clarify the diagnostic performance and neural basis of the Clock Drawing Test (CDT) combining free‐ and pre‐drawn methods. Methods: This retrospective study included 165 participants (91 with Alzheimer disease [AD], 52 with amnestic mild cognitive impairment [aMCI], and 22 healthy controls [HC]), who were divided into four groups according to their free‐ and pre‐drawn CDT scores: group 1, could do both; group 2, impaired in both; group 3, impaired in pre‐drawn CDT; and group 4, impaired in free‐drawn CDT. The diagnostic performances of the free‐drawn, pre‐drawn, and combination methods were compared using receiver operating characteristics analysis; in voxel‐based morphometry analysis, the gray matter (GM) volume of groups 2–4 were compared with that of group 1. Results: The area under the curve of the combination method was greater than that of the free‐ or pre‐drawn method alone when comparing AD with HC or aMCI. Group 2 had a significantly smaller GM volume in the bilateral temporal lobes than group 1. Group 3 had a trend toward smaller GM volumes in the right temporal lobe when a liberal threshold was applied. Group 4 had significantly smaller GM volumes in the left temporal lobe than group 1. Conclusions: This study suggests that the combination method may be able to screen for a wider range of brain dysfunction. Combined use of free‐ and pre‐drawn CDT may be useful for screening for AD and its early detection and treatment. Key points: The diagnostic performance and neural basis of the combination of free‐ and pre‐drawn Clock Drawing Test (CDT) were investigated in the Alzheimer disease [AD] continuum. The combination method is more sensitive than each method alone as a screening test for AD. The combination can screen for a wider range of brain dysfunction than each method alone.